Advances in cell-based biosensors: Transforming food flavor evaluation with novel approaches - Mahmoud Said Rashed; Esraa A. Abdelkarim; Tamer Elsamahy; Mabrouk Sobhy; Hany S. El-Mesery; Ali Salem (Food Chemistry: X)
Food flavor, a blend of taste and smell, is key to consumer acceptance and food quality. Traditional sensory and instrumental methods often fail to replicate human sensory responses. This review discusses the role of cell-based biosensors in flavor evaluation, showcasing their sensitivity, specificity, and rapid response. Using living cells like taste and olfactory cells, these biosensors surpass traditional approaches. Advancements include microelectrode array systems with taste receptor cells for real-time detection of bitter, sweet, and umami substances and improved cell immobilization technologies for detecting complex odorant profiles. Challenges such as signal stability, selective detection, cell cultivation, and scalability persist. However, integrating artificial intelligence and portable technologies could broaden their applications. With the potential to revolutionize sensory analysis, cell-based biosensors offer a sustainable, precise, and scalable approach to food flavor evaluation, bridging sensory perception with advanced analytical methods and driving innovation in food science.